Смещение частоты плазмонного резонанса при изменении во времени показателя преломления внешней среды нанопровода - Стогний, Н. П.; Сахненко, Н. К. (ХНУРЭ, 2013)
In this paper, a 2D problem of surface plasmon transformation due to time variation of silver nanowire environment is analytically solved. Solution of the problem is constructed in the form of the Laplace transform. Accurate time domain inversion has made it possible to analyze transient and steady state regimes.
Keywords: нанопровод; поверхностный плазмон; переходные процессы